Limit Equilibrium Method for Stability Analysis of Dangerous Rock Considering Surrounding Rock Constraints - SU Guoshao; ZHANG Jixiang; LIU Youneng; WANG Junmu (Renmin Zhujiang)
The current code exhibits limitations in conducting stability analyses of dangerous rock with complex shapes and fails to consider the effects of multiple structural planes. This study improved the existing limit equilibrium method according to the characteristics of dangerous rock with complex shapes and shear stress distribution based on three-dimensional discrete element calculation. The proposed method considered the constraint effects of the back margin for dangerous rock of falling and sliding types with structural surfaces controlled by the upper margin and lower margin, respectively. For sliding-type dangerous rock with double structural surfaces, the influence of the fissure water pressure on the back margin was considered. The stability analysis of these three types of dangerous rock was conducted by the improved limit equilibrium method. Compared with the simulation results of the three-dimensional discrete method, it is shown that the improved formula can be used to calculate the stability coefficients of dangerous rock with different complex shapes under the influence of multiple structural planes. The relative error is only 3.06%–9.10%. Compared with a relative error of 13.8%–14.7% of the recommended formula in the code, the calculation accuracy is significantly improved. The improved formula fully considers the characteristics of the surrounding constraints of dangerous rock, providing an idea for the limit equilibrium method to address challenges associated with dangerous rock with complex shapes.